Adapting to teaching restrictions during the COVID-19 pandemic in Japanese universities - Adam L. Miller (Academy of Cognitive and Natural Sciences, 2022)
Due to the COVID-19 pandemic, a number of States of Emergency were announced in Japan, that drastically and suddenly shifted teaching practices in tertiary education. This study explores how teachers working within this field navigated this pedagogical shift. Furthermore, examples will be given for both the potential restrictions and benefits of utilizing distance learning in EFL tertiary education. The research is based upon both a review of existing literature concerned with EFL education, as well as two qualitative interviews with university teachers based in Japan. The collected data underwent thematic analysis, and the results indicated that complications were brought about by this new teaching approach, such as a lack of social interaction. However, some benefits were also apparent, such as stakeholders becoming more familiar with instructional technology, or the discovery of more effective teaching methods. This study aims to look at how this technology may be used in the future to not only alleviate pressure brought about by extreme circumstances, but also to enrich the learning environment in contemporary tertiary education settings in Japan.